2012
DOI: 10.3390/ph5020114
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Antagonists and Chronic Pain: Beyond Thermal Perception

Abstract: Abstract:In the last decade, considerable evidence as accumulated to support the development of Transient Receptor Potential Vanilloid 1 (TRPV1) antagonists for the treatment of various chronic pain conditions. Whereas there is a widely accepted rationale for the development of TRPV1 antagonists for the treatment of various inflammatory pain conditions, their development for indications of chronic pain, where conditions of tactical, mechanical and spontaneous pain predominate, is less clear. Preclinical locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 73 publications
1
35
0
Order By: Relevance
“…Our results demonstrate that capsaicin, capsazepine, BCTC, and A-889425 are effective Ca v 3 channel inhibitors at concentrations well below those used clinically to produce analgesia (Brandt, Beyer, & Stahl, 2012). Interestingly, Palvanil, AMG9810, and resiniferatoxin did not modulate Ca v 3 channels despite being structurally and chemically related to the other TRPV1-active compounds tested (Figure 2a).…”
Section: Discussionmentioning
confidence: 73%
“…Our results demonstrate that capsaicin, capsazepine, BCTC, and A-889425 are effective Ca v 3 channel inhibitors at concentrations well below those used clinically to produce analgesia (Brandt, Beyer, & Stahl, 2012). Interestingly, Palvanil, AMG9810, and resiniferatoxin did not modulate Ca v 3 channels despite being structurally and chemically related to the other TRPV1-active compounds tested (Figure 2a).…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, it has recently been shown that intra-articular administration 632 of a TRPV1 antagonist attenuated early osteoarthritic pain in a mono-sodium iodoacetate model 633 of osteoarthritis(Haywood et al, 2018). Historically in pre-clinical models, TRPV1 antagonists 634 attenuated thermal hyperalgesia, but their efficacy in mechanical hyperalgesia and ongoing pain is 635 unclear(Brandt et al, 2012). The peripherally restricted TRPV1 antagonist, A-425619, has been 636 previously shown to reverse thermal and mechanical hypersensitivity in rat CFA models and also 637 restore weight bearing ability in rat osteoarthritis models(Honore et al, 2005).…”
mentioning
confidence: 99%
“…The role of TRPV1 in inflammatory pain has been the thoroughly studied. Many different inflammatory mediators, including BK, PGE 2 and NGF have been shown to cause phosphorylation of TRPV1 and increase channel activity [81,[99][100][101].…”
Section: The Role Of Trpv1 In Pain Conditionsmentioning
confidence: 99%
“…Additionally, mildly acidic inflammatory conditions can decrease the activation thresholds of TRPV1 [102,103]. Furthermore, inhibition of TRPV1 can lead to decreases in thermal and mechanical hypersensitivity in animal models of inflammatory pain [99]. Early clinical trials with TRPV1 antagonists show that inhibiting TRPV1 results in decreased thermal pain perception [104].…”
Section: The Role Of Trpv1 In Pain Conditionsmentioning
confidence: 99%
See 1 more Smart Citation